IMPLEMENTASI KEBIJAKAN PROGRAM PENDIDIKAN ANAK USIA DINI (PAUD) PADA DINAS PENDIDIKAN DAN KEBUDAYAAN DAERAH PROVINSI SULAWESI TENGAH - Nunu, Sehi (Katalogis, 2017)
Early Childhood Education (ECD) Program is one of the educational service programs to educate the people and make them healthy physically and mentally. This is in accordance with the mandate of the 1945 Constitution which states that all citizens of the Republic of Indonesia have the rights to gain educational opportunities and accesses that are equal, full of quality, relevant, and competitive according to their interests, talents, and abilities regardless of social statuses, ethnicities, and genders in all corners of the country. Based on that, the problems to be studied were how the implementation of the ECD Program Policy at Central Sulawesi Department of Education and Culture and what factors influencing the implementation of that policy in the region of Central Sulawesi Province. The purposes of this study were to determine and analyze the process and the factors influencing the process. The uses of this study were both academical (theoretical) and practical uses.The research method used was qualitative. Data collection techniques were observation, interview, and literature research. The results showed that the implementation of the ECD Program Policy at Central Sulawesi Department of Education and Culture and some of ECD institutions was influenced by four aspects, namely communication, resources, disposition, and bureaucratic structure. The implementation of the ECD Program at Central Sulawesi Department of Education and Culture involving ECD institutions in the region of Central Sulawesi Province had not been running maximally. The communication aspect: Coordination among the implementors of the ECD Program had not been running properly and optimally, resulting in miscommunications that caused the implementation not running optimally as expected. The resources aspect was also less effective, either in terms of human resources, facilities, infrastructures, or financial resources (budget).